Prognostic role of neuroendocrine differentiation in prostate cancer, putting together the pieces of the puzzle - Berruti, Alfredo (Dove Medical Press, 2010)
Neuroendocrine (NE) differentiation is a common feature in prostate cancer (PC). The clinical significance of this phenomenon is controversial; however preclinical and clinical data are in favor of an association with poor prognosis and early onset of a castrate resistant status. NE PC cells do not proliferate, but they can stimulate the proliferation of the exocrine component through the production of paracrine growth factors. The same paracrine signals may favor the outgrowth of castrate adapted tumors through androgen receptor dependent or independent mechanisms. Noteworthy, NE differentiation in PC is not a stable phenotype, being stimulated by several agents including androgen deprivation therapy, radiation therapy, and chemotherapy. The proportion of NE positive PC, therefore, is destined to increase during the natural history of the disease. This may complicate the assessment of the prognostic significance of this phenomenon. The majority of clinical studies have shown a significant correlation between NE differentiation and disease prognosis, confirming the preclinical rationale. In conclusion the NE phenotype is a prognostic parameter in PC. Whether this phenomenon is a pure prognostic factor or whether it can influence the prognosis by favoring the onset of a castrate resistance status is a matter of future research.